A conjugate gradient method with Strong Wolfe-Powell line search for unconstrained optimization - Mustafa, Mamat; Mohamed, Hamoda; Mohd Rivaie, Mohd Ali (Hikari Ltd., 2016)
In this paper, a modified conjugate gradient method is presented for solving large-scale unconstrained optimization problems, which possesses the sufficient descent property with Strong Wolfe-Powell line search. A global convergence result was proved when the (SWP) line search was used under some conditions. Computational results for a set consisting of 138 unconstrained optimization test problems showed that this new conjugate gradient algorithm seems to converge more stable and is superior to other similar methods in many situations.